Potential of flavonoids as entry inhibitors for dengue virus type-2 using molecular dynamics simulation and molecular docking / Nurul Azira Ismail - Ismail, Nurul Azira (2019)
Dengue infections are currently estimated to be 390 million cases annually. Yet, there is no vaccine or specific therapy available. Envelope glycoprotein E (E protein) of DENV mediates viral attachment and entry into the host cells. Several flavonoids have been shown to inhibit HIV-1 and hepatitis C virus entry during the virus–host membrane fusion. Herein, we report the findings from protein modelling, molecular dynamics simulation and docking of the E-M heterodimer model of DENV type-2 for Malaysia (DENV2-My) in an attempt to suggest the entry inhibitor for DENV. Two main interactions discovered during molecular dynamics simulation of both DENV2- My and its template, DENV2-Thai, in both different conditions; normal and low pH conditions. Hydrophobic contacts were mainly observed between the N-terminal loop of M protein and the soluble ectodomain E protein in three different pockets. In addition, hydrogen bond interactions were discovered between the stem-anchor region of the E and M proteins. Both interactions diminished at low pH due to the increasing of distance between the E and M proteins triggered by the low pH. This reduction leads to the assumption that both interactions control the conformational change that responsible in the dissociation between E and M during the virus maturation and fusion. Molecular docking method was employed to predict the binding of nine flavonoids (baicalin, baicalein, EGCG, fisetin, glabranine, hyperoside, ladanein, quercetin and flavone) to the soluble domain E protein of both DENV2. Eight flavonoids were found to dock into the same binding pocket located between the domain I and domain II of different subunits of E protein. Consistent docking results were observed not only for both DENV2 but also for the E protein structures of tickborne encephalitis virus and Japanese encephalitis virus. Apart from docking, molecular dynamics simulations were performed to further evaluate the interaction profile of the docked E protein-flavonoid complexes. Ile4, Gly5, Asp98, Gly100, and Val151 residues of DENV2-My are dominantly forming hydrogen bonds with baicalein, quercetin, and EGCG during the simulations. In computational studies, our proposed flavonoids binding pocket could be potentially used as a drug discovery target and the selected flavonoids confirm promising results to work as potential entry inhibitors for dengue infection. Further experimentation on the proposed flavonoids can result in the development of strong inhibitors.